Problem Based Learning Untuk Meningkatkan Keaktifan dan Motivasi Belajar Peserta Didik Kelas II di SDN Dukuh Menanggal I - Ummayasri (Universitas PGRI Adi Buana Surabaya, 2021)
Student activity and learning motivation of class II students are still low, so it is necessary to implement a Problem Based Learning model to improve it. This study aims to increase student activity and motivation in learning theme 9 through the Problem Based Learning model in class II Semester 2 SDN Dukuh Menanggal I. This research is a classroom action research conducted in three cycles consisting of two meetings each cycle. Data collection techniques on student research, questionnaires and observation sheets. The results of the study after using the Problem Based Learning model in the first cycle showed an increase of 57. In the second cycle there was an increase with the acquisition of the average value of student activity reaching 71 and Cycle 3 experiencing a significant increase seen from the average results obtained. get reached 84 students' learning motivation in cycle 1 obtained the average value of student activity reached 53. Cycle 2 the average value of student learning motivation reached 70. There was an increase in cycle 3 which was quite significant seen from the average results obtained reached 86. It was concluded that the Problem Based Learning model could increase students' activeness and motivation in learning the theme of 9th grade class II Semester 2 SDN Dukuh Menanggal I.